PENGARUH EXPERIENTIAL LEARNING MODEL TERHADAP SCIENTIFIC LITERACY PESERTA DIDIK SMP - Nisrochah, Nisrochah; Wilujeng, Insih (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
The purpose of this study was to reveal the effect experiential learning model on scientific literacy. Scientific literacy is often used as one of the goals of learning science because scientific literacy reflects the ability of students to apply scientific knowledge possessed in daily life in different circumstances and situations. Scientific literacy consist of contexts, knowledge, competencies, and attitudes. This study is a quasi-experimental research using nonrandomized control group, pretest-posttest design. The study was conducted at three schools, each school representing high school, medium school, and low school. The results showed that the scientific literacy of students in the experimental class has increased higher than students in the control class, both at the high school, medium school, and low school categories. This is because experiential learning model enable students to develop the knowledge, skills, values and attitudes through direct experience. Experiential learning model can improve scientific literacy of students through a four-stage of experiential learning model that is concrete experience, reflective observation, abstract conceptualization, and active experimentation.